Outcomes of Mothers and Infants Affected by COVID-19 - Daniel, Katherine B.; Olague, Stefany; Boyle, Helen; Ahmed, Imtiaz; Buchh, Basharat; Truong, Giang Sinh T.; Reyburn, Brent; DeLeon, Clarissa; Lin, Grace C.; Ahmad, Kaashif A.; Carr, Barbara; Singhal, Meghali; Althouse, Melissa; Castro, Raymond; Rudine, Anthony; Rider, Evelyn; Macomber-Estill, Melissa L.; Doles, Bradley; Ferry, Jenelle F.; Pierantoni, Hector; Sutherland, Savannah; Kelleher, Amy S.; Clark, Reese H.; Blackwell, Courtney K.; Smith, P. Brian; Benjamin, Daniel K., Jr.; Greenberg, Rachel G. (American Journal of Perinatology, 2025)
The long-term effects of the novel coronavirus disease 2019 (COVID-19) infection during pregnancy are poorly characterized in mothers and their infants. The aim of this study was to assess the physical, mental, and emotional well-being of mothers and infants in the first year postpartum who were exposed to and/or diagnosed with COVID-19 infection.This direct-to-participant cohort study recruited 96 mother–infant pairs delivering at Pediatrix Medical Group sites, where mothers tested positive for COVID-19 during their pregnancy or birth hospitalization and/or infants tested positive for COVID-19 prior to hospital discharge. Main outcome measures included scored responses to surveys administered at 6 and 12 months postpartum and infant health status from newborn admission through the first year after birth.Mothers with COVID-19 infection during pregnancy often reported persistent physical, mental, and emotional stress affecting both themselves and their infants. Scores assessing infant temperament were higher than reported in prior literature. Infants were relatively healthy throughout their first year after birth.The experience of COVID-19 infection during pregnancy may create a unique set of circumstances that affects the well-being of infants and their mothers separately as well as the child-caregiver relationship. Early life events have the potential to generate lasting consequences; therefore, it is important to identify these issues to maximize support and intervene if indicated.
Keywords: pregnancy; infant; COVID-19; mood; stress